2010
DOI: 10.1603/ec09093
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Spinosad (Naturalytes) in Controlling the Cowpea Storage Pest, <I>Callosobruchus maculatus</I> (Coleoptera: Bruchidae)

Abstract: The biopesticide Spinosad controls many insect pests of stored-food products. Laboratory and field trials were carried out to determine the efficacy of this pesticide against the cowpea weevil, Callosobruchus maculatus (F.) (Coleoptera: Bruchidae), the main storage pest of cowpea, Vigna unguiculata, Walp, in West Africa. In the laboratory, Spinosad caused high mortality of adult C. maculatus and decreased the number of eggs laid by females. Spinosad, however, was less toxic in the 24 h treatment to C. maculatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 19 publications
(20 reference statements)
1
22
0
1
Order By: Relevance
“…No seed infestation was recorded when seeds were treated with 1000 ppm of spinosad resulting in maximum inhibition rate (100.00%) ( Table 4). The present research is supported by Sanon et al (2010) observed that less than 20% of the seeds were perforated in the spinosad treatment and controlled C. maculatus throughout the 6 months of cowpea storage. Bonjour et al (2006), Islam et al (2007) and Athanassiou et al (2008) reported similar effects of spinosad.…”
Section: Effect Of Spinosad On Seed Infestation (%)supporting
confidence: 79%
“…No seed infestation was recorded when seeds were treated with 1000 ppm of spinosad resulting in maximum inhibition rate (100.00%) ( Table 4). The present research is supported by Sanon et al (2010) observed that less than 20% of the seeds were perforated in the spinosad treatment and controlled C. maculatus throughout the 6 months of cowpea storage. Bonjour et al (2006), Islam et al (2007) and Athanassiou et al (2008) reported similar effects of spinosad.…”
Section: Effect Of Spinosad On Seed Infestation (%)supporting
confidence: 79%
“…A summary of ecotoxicology data for spinosad (SPI) is provided in Table 8 . This insecticide is used for the control of caterpillars [272-274,317], thrips [275], beetle and fly pests in a range of fruit and vegetable crops [276-278], ornamentals, turf [279], and stored grains [280-282]. SPI is also used against mosquitos [283-285] and flies [286] as well as tsetse fly [287] control.…”
Section: Ecotoxicity Of Spinosynsmentioning
confidence: 99%
“…Chemical pesticides, mostly belonging to four chemical groups – organochlorines, organophosphates, carbamates and pyrethroids, have been used in fields and storage for over five decades for the management of insect pests, including bruchids (Dent, ; Megerssa, ). The use of spinosad, a natural biopesticide component has appeared to be effective for the management of these storage pests either in laboratory or in field conditions (Sanon et al ., ). The application of spinosads reduced the emergence of C. maculatus and perforation of seeds after 6 months of storage in cowpea.…”
Section: Conventional Approachesmentioning
confidence: 97%